2019
DOI: 10.25149/jcrm.v8i2.179
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent congenital pseudoaneurysm of mitral-aortic intervalvular fibrosa and left sinus of Valsalva aneurysm

Abstract: Either the pseudoaneurysm of mitral-aortic intervalvular fibrosa or the aneurysms of Valsalva are rare cardiac conditions. Concomitant diagnosis in the same patient is extremely rare with only one case report. Herein, we described an extremely rare case of concomitant pseudoaneurysm of mitral-aortic intervalvular fibrosa and aneurysm of left sinus of Valsalva in 21-year-old black man admitted with new-onset of heart failure (NYHA class III) diagnosed by transesophageal echocardiography. Despite medical therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In the present review, no cases of BAV were found, and VSD was found in only 4.3% of cases (one patient). In turn, SOVAs are associated with other congenital aneurysms, such as submitral aneurysms [16], fibrous mitral-aortic aneurysm [18], coronary artery aneurysm [14] and membranous septum [6]. This was a frequent finding in our review.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…In the present review, no cases of BAV were found, and VSD was found in only 4.3% of cases (one patient). In turn, SOVAs are associated with other congenital aneurysms, such as submitral aneurysms [16], fibrous mitral-aortic aneurysm [18], coronary artery aneurysm [14] and membranous septum [6]. This was a frequent finding in our review.…”
Section: Discussionmentioning
confidence: 53%
“…A total of 48 papers were identified, of which 28 records not related to the theme were excluded. A total of 20 full-text papers representing 23 patients, children and adults included, were included in this review [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations